N2S2 pyridinophane-based fluorescent chemosensors for selective optical detection of Cd2+ in soils. (24th November 2020) - Garau, Alessandra; Lvova, Larisa; Macedi, Eleonora; Ambrosi, Gianluca; Aragoni, M. Carla; Arca, Massimiliano; Caltagirone, Claudia; Coles, Simon J.; Formica, Mauro; Fusi, Vieri; Giorgi, Luca; Isaia, Francesco; et al.
Abstract : A fluorescent sensor array for the quantitative determination of Cd 2+ in soils based on two N2 S2 pyridinophane chemosensors is presented. Abstract : Herein we describe the synthesis and coordination properties in solution towards Zn 2+ and Cd 2+ of the ligands L1 and L2 containing the 2, 8-dithia-5-aza-2, 6-pyridinophane (L ) macrocyclic receptor unit and the 2-(2′-hydroxy-3′-naphthyl)-4-methylbenzoxazole (HNBO) or 7-(2-ethylamino)-4-methylcoumarin chromophores. Spectrophotometric and spectrofluorimetric measurements in the UV-visible region (MeCN/H2 O solution 4 : 1 v/v) and 1 H NMR measurements provided insight into the nature of complex species and transduction mechanisms responsible for the optical responses. The ligands showed an OFF–ON response upon addition of Zn 2+ and Cd 2+, for L1, and only Cd 2+, for L2, in both cases attributable to the formation of 1 : 1 metal-to-ligand complexes. The crystal structure of [CdL2 (NO3 )2 ] is reported, Cd 2+ being heptacoordinated by L and NO3 − anions in a N2 S2 O3 environment. Exploiting the fluorescence properties of L1 and L2, an optical sensor array was developed featuring PVC membranes containing the dispersed sensing material and based on the Photoassisted Technique (PT) for signal acquisition, which allowed a quantitative determination of Cd 2+ in real samples (soils). All phases from the design of the chemosensors to the development of the sensing device are discussed.